Unilateral inactivation of the basolateral amygdala attenuates context-induced renewal of Pavlovian-conditioned alcohol-seeking - Chaudhri, N. (2013)
Environmental contexts associated with drug use promote craving in humans and drug-seeking in animals. We hypothesized that the basolateral amygdala (BLA) itself, as well as serial connectivity between the basolateral amygdala (BLA) and nucleus accumbens core (NAC core), were required for context-induced renewal of Pavlovian-conditioned alcohol-seeking. Male, Long-Evans rats were trained to discriminate between two conditioned stimuli (CS) - a CS+ that was paired with ethanol (EtOH, 20%, v/v) delivery into a fluid port (0.2 ml/CS+, 3.2 ml/session) and a CS− that was not. Entries into the port during each CS were measured. Next, rats received extinction in a different context where both cues were presented without EtOH. At test, responding to the CS+ and CS− without EtOH was evaluated in the prior training context. Control subjects showed a selective increase in CS+ responding relative to extinction, indicative of renewal. This effect was blocked by pre-test, bilateral inactivation of the BLA using a solution of gamma-amino-butyric-acid receptor agonists (0.1 mM muscimol and 1.0 mM baclofen; M/B; 0.3 µl/side). Renewal was also attenuated following unilateral injections of M/B into the BLA, combined with either M/B, the dopamine D1 receptor antagonist SCH 23390 (0.6 µg/side), or saline infusion in the contralateral NAC core. Hence, unilateral BLA inactivation was sufficient to disrupt renewal, highlighting a critical role for functional activity in the BLA in enabling the reinstatement of alcohol-seeking driven by an alcohol context.